ROBOTICS AND SENSOR SYSTEMS USED IN REHABILITATION EQUIPMENT (International journal of artificial intelligence, 2025)
The integration of robotics and sensor systems in rehabilitation equipment represents a transformative approach in modern physiotherapy and assistive technologies. This article explores the design, implementation, and clinical applications of robotic rehabilitation devices enhanced with high-precision sensors. These systems enable real-time monitoring of patient movements, muscle activity, and biomechanical parameters, allowing for adaptive therapy that responds to individual patient needs. By combining robotic actuation with sensor feedback, rehabilitation equipment can optimize exercise intensity, improve motor learning, and accelerate recovery while reducing the risk of injury. The paper also highlights the role of artificial intelligence algorithms in processing sensor data to personalize rehabilitation protocols, track progress, and provide predictive insights for therapy adjustments. Furthermore, the study discusses recent technological advancements, including wearable exoskeletons, force-sensitive manipulators, and smart physiotherapy platforms, demonstrating their effectiveness in restoring mobility and enhancing quality of life for patients with neurological, musculoskeletal, and post-operative conditions.